2012
DOI: 10.1111/j.1365-2672.2012.05305.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of qPCR permutations, internal controls and dilution as means for minimizing the impact of inhibition while measuring Enterococcus in environmental waters

Abstract: Aims:  Draft criteria for the optional use of qPCR for recreational water quality monitoring have been published in the United States. One concern is that inhibition of the qPCR assay can lead to false‐negative results and potentially inadequate public health protection. We evaluate the effectiveness of strategies for minimizing the impact of inhibition. Methods and Results:  Five qPCR method permutations for measuring Enterococcus were challenged with 133 potentially inhibitory fresh and marine water samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 21 publications
5
118
0
Order By: Relevance
“…Salmon sperm DNA has been used as a dual control for recovery through sample processing and inhibition (54). Cao et al (9) compared the efficacy of four internal controls to that of sample dilution and concluded the following: (i) sample dilution provided the most reliable and readily interpretable evidence for inhibition, (ii) PCR chemistry, including the specific polymerase master mix used, had a major influence on the frequency of inhibited samples, and (iii) the choice of method to assess inhibition is not yet agreed upon and may vary by site or study objective.…”
Section: Discussionmentioning
confidence: 99%
“…Salmon sperm DNA has been used as a dual control for recovery through sample processing and inhibition (54). Cao et al (9) compared the efficacy of four internal controls to that of sample dilution and concluded the following: (i) sample dilution provided the most reliable and readily interpretable evidence for inhibition, (ii) PCR chemistry, including the specific polymerase master mix used, had a major influence on the frequency of inhibited samples, and (iii) the choice of method to assess inhibition is not yet agreed upon and may vary by site or study objective.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were considered inhibited if the ΔC q between 5-fold dilutions was less than 1.3, which is one cycle less than expected amplification assuming 100% efficiency, as recommended by Cao and others. 19 Statistical analysis. Stata version 13.1 (StataCorp LP, College Station, TX) was used for all data analysis with the primary goal of determining if child soil ingestion was associated child diarrhea in the past 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…19 For samples classified as quantifiable (C q < 32), 5-fold dilutions were completed using each sample's DNA extract. For samples that were classified as DNQ or ND, a subset of these samples was evaluated for inhibition by spiking 3 × 10 3 copies/μL into the DNA extract before completing 5-fold dilutions to measure the linearity of response.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies identified that neat DNA extracts and 10-fold dilutions of sample must be run in parallel when performing the T. orientalis cPCR assays to account for PCR-inhibiting contaminants present within nucleic acid extracts prepared from blood (6,19,27). To overcome this, we used a DNA polymerase master mix that has been demonstrated to be effective at reducing contaminant-based inhibition (TaqMan environmental master mix) (42). We assessed the efficacy of this master mix in reducing or eliminating the effects of PCR inhibition during development of the UIC assay.…”
Section: Fig 1 the U Component Of The Uic Assay Is Quantitative (A) mentioning
confidence: 99%